Video game play among adolescents : gender differences and effects on anger and physical aggression - Anna Jóna Reynisdóttir 1991- (2016)
Evidence of the effects of playing video games on children’s anger and aggression has been mixed. This study examined the following hypotheses: 1) Video game play would have an effect on anger and physical aggression, 2) The more video game play the higher levels of anger and aggression in both genders, 3) There would, as a result of video game play, be a difference in aggression and anger between the genders, boys would show higher levels. The current study was based on archival data from the Icelandic Centre for Social Research and Analysis (ICSRA), Youth in Iceland 2014. Four questions from the questionnaire were used and the study used responses from a random sample from the population which included 2055 participants. Students who spent no time playing video games were excluded from the study leaving 775 participants, 559 boys and 202 girls. The participants’ age was between 13 and 18 years. The results confirmed that video game play did not have a significant effect on anger or aggression. However, they specify a significant interaction between gender and time spent playing video games on aggression. Conclusions were that gender plays an important role in how video games affect adolescents’ aggression. Niðurstöður um áhrif þess að spila tölvuleiki á reiði og árásargirni unglinga hafa verið af mismunandi toga. Rannsókn þessi skoðaði eftirfarandi tilgátur: 1) tölvuleikir hafa áhrif á reiði og líkamlega árásargirni, 2) því meiri tölvuleikjaspil því hærra stig reiði og árásargirni hjá báðum kynjum, 3) það er munur á áhrifum tölvuleikjaspila á árásarhneigð og reiði á milli kynjanna, strákar sýna hærri stig. Núverandi rannsókn var byggð á gögnum frá Rannsóknum og greiningu (R&G), Ungt fólk 2014. Notaðar voru fjórar spurningar úr spurningalistanum og rannsóknin notaði svör slembiúrtaks úr þýði sem innihélt 2055 þátttakendur. Þeir nemendur sem eyddu engum tíma í að spila tölvuleiki voru útilokaðir frá rannsókninni og eftir voru 775 þátttakendur, 559 drengir og 202 stúlkur. Þátttakendur voru á aldrinum 13 til ...